Implementation of Integrated Quality Management in Nursing Services - Rossa, M. Adila; Darmojo, Hardjito S (LPPM AKPER FATMAWATI, 2020)
Integrated Quality Management (IQM) is a strategic approach oriented towards continuous improvement to enhance the quality of healthcare services, including nursing care. Nurses, as frontline care providers, play a crucial role in ensuring patient quality and safety. Therefore, the implementation of IQM in nursing care is a relevant issue that merits in-depth study. This study aims to explore the implementation of IQM in nursing care and identify supporting factors, barriers, and its impact on service quality. The study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, participant observation, and document review in the nursing care unit. The informants included nurses, ward heads, nursing managers, and the quality management team, selected purposively. Data were analyzed using thematic analysis to identify key patterns and themes. The results indicate that the implementation of IQM in nursing care has been ongoing, but remains partial and tends to be administrative. Nursing leadership and active nurse involvement play a crucial role in the success of IQM implementation. Key barriers include high workload, limited resources, and lack of ongoing training. Nevertheless, the implementation of Integrated Quality Management (TMM) has had a positive impact on compliance with care standards, nursing documentation, and patient safety awareness. This study concludes that strengthening a culture of quality, visionary leadership, and nurse empowerment are necessary to optimize the implementation of Integrated Quality Management (TMM) in nursing services